Diversity of bivalves on the north coast of Lamongan, East Java, Indonesia - Viola Atlanta; Reni Ambarwati; Dwi Anggorowati Rahayu; Nova Mujiono (Society for Indonesian Biodiversity, 2022)
Abstract. Atlanta V, Ambarwati R, Rahayu DA, Mujiomo N. 2022. Diversity of bivalves on the north coast of Lamongan, East Java, Indonesia. Biodiversitas 23: 4263-4271. Biodiversity in Indonesian waters is very abundant, one of which is bivalves. This study aimed to analyze the diversity, abundance, uniformity and dominance of bivalves, as well as to analyze the habitat profile of bivalves in the North Coast of Lamongan. Bivalves sampling was carried out at Kutang Beach and Joko Moersodo Beach. There were three research stations consisting of three sub-stations on each beach. At each sub-station, it was taken the plot of 5×5 m. Each plot contained five subplots of 1×1 m. The habitat profiles studied were temperature, pH, salinity, and turbidity and the type of substrate. Samples were identified based on morphological characters. The research data obtained were analyzed descriptive qualitatively. The results revealed that the bivalves found in the North Coast of Lamongan included Anadara antiquata, Vasticardium elongatum, Donax faba, Asaphis sp., Gari elongata, Serratina perplexa, Gafrarium pectinatum, Heterocardia gibbosula, Marcia hiantina, Marcia japonica, Marcia opima, Meretrix sp., and Venerupis aspera. The index value of bivalves’ diversity at the North Coast of Lamongan was 1.13-2.201. The habitat profile of the bivalves in the North Coast of Lamongan was as follows: temperature 29.3-31.7ºC, salinity 25-32 ppt, pH 7.59-8.18, turbidity 10.6-17.3 NTU and the dominant type of substrate was sandy mud. Bivalves were more commonly found on beaches with dense mangroves.